A high salt meal does not impair cerebrovascular reactivity in healthy young adults. Issue 19 (10th October 2020) - Migdal, Kamila U.; Robinson, Austin T.; Watso, Joseph C.; Babcock, Matthew C.; Lennon, Shannon L.; Martens, Christopher R.; Serrador, Jorge M.; Farquhar, William B.
Abstract: A high sodium (Na + ) meal impairs peripheral vascular function. In rodents, chronic high dietary Na + impairs cerebral vascular function, and in humans, habitual high dietary Na + is associated with increased stroke risk. However, the effects of acute high dietary Na + on the cerebral vasculature in humans are unknown. The purpose of this study was to determine if acute high dietary Na + impairs cerebrovascular reactivity in healthy adults. Thirty‐seven participants (20F/17M; 25 ± 5 years; blood pressure [BP]: 107 ± 9/61 ± 6 mm Hg) participated in this randomized, cross‐over study. Participants were given a low Na + meal (LSM; 138 mg Na + ) and a high Na + meal (HSM; 1, 495 mg Na + ) separated by ≥ one week. Serum Na +, beat‐to‐beat BP, middle cerebral artery velocity (transcranial Doppler), and end‐tidal carbon dioxide (PET CO2 ) were measured pre‐ (baseline) and 60 min post‐prandial. Cerebrovascular reactivity was assessed by determining the percent change in middle cerebral artery velocity to hypercapnia (via 8% CO2, 21% oxygen, balance nitrogen) and hypocapnia (via mild hyperventilation). Peripheral vascular function was measured using brachial artery flow‐mediated dilation (FMD). Changes in serum Na + were greater following the HSM (HSM: Δ1.6 ± 1.2 mmol/L vs. LSM: Δ0.7 ± 1.2 mmol/L, p < .01). Cerebrovascular reactivity to hypercapnia (meal effect: p = .41) and to hypocapnia (meal effect: p = .65) were not affected by the HSM. Contrary with previous findings, FMD was not reduced following the HSM (meal effect: p = .74). These data suggest that a single high Na + meal does not acutely impair cerebrovascular reactivity, and suggests that despite prior findings, a single high Na + meal does not impair peripheral vascular function in healthy adults. Abstract : A single high sodium meal compared to a low sodium meal does not impair cerebrovascular reactivity to hypercapnia or hypocapnia in healthy adults. MCA, Middle Cerebral Artery.